Faktor Pengaruh Nilai Penempatan Deposito Rupiah Nasabah Individu di Jabodetabek - Aloysius Raino Bawono Miranda (Studi Akuntansi dan Keuangan Indonesia, 2017)
This research aims to investigate the factors that significantly affect the placement of customer funds on BUKU 4 banks’ time-deposits in Jabodetabek. Researcher use the questionnaires that were distributed to 405 respondents to capture perceptions on factors that have been tested previously, such as interest rate, service facilities, and promotion. Researcher added the trust factor and word-of-mouth variables in this study. The result is the interest rate and trust factor have a significant impact on the placement of customer’s funds on BUKU 4 banks’ time- deposit in Jabodetabek. While the service quality, word of mouth, and promotion do not affect significantly. Keywords: bank’s time deposit, interest rate, service quality, trust, word-of-mouth, promotion https://doi.org/10.21632/saki.1.1.43-53